Research of Cylindrical Linear Induction Motor with Unconventionally Connected Windings - Poska, A. J.; Buksnaitis, J. (Elektronika ir Elektrotechnika, 2012)
The changes of cylindrical linear induction motor (CLIM) starting force due to electric drive operation matching by changing the connection circuit of polysolenoid CLIM inductor winding coils are analyzed. The starting force measurements were carried out under different connections of CLIM winding coils and their relative magnitudes were determined. Also the research of electromagnetic properties of winding coils connected in some certain way was performed. It was determined that when changing phase winding polarities, it is possible to reduce the starting force by some certain amount, and when coil terminals are short-circuited or the coil is removed from the winding, the same force can be increased, compared to force generated by conventionally connected coils. The electromagnetic efficiency factor for conventionally connected winding coils was determined: kef = 0,699. When changing polarity of one coil of the winding, this factor decreased down to kef = 0,626, and when the coil is removed from the winding, factor increased up to kef = 0,715. This proves that the electromagnetic efficiency of CLIM inductor winding indirectly indicates the starting force of this motor. Ill. 5, bibl. 6, tabl. 3 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.121.5.1646